Hubungan Pengetahuan Dan Motivasi Dengan Kepatuhan Minum Obat Pada Pasien TB Paru Di RS Malahayati Medan - Pakpahan, Jun Edy Samosir (Universitas Aufa Royhan, 2024)
Pulmonary tuberculosis (TB) is a public health problem that, in Indonesia, is even the number one killer among other infectious diseases. An obstacle in TB treatment is the lack of compliance of TB sufferers with taking anti-tuberculosis medication. The cause is the lack of motivation of sufferers. The aim of this research was to determine the relationship between knowledge, motivation, and medication adherence in pulmonary TB patients at Malahayati Hospital, Medan. This research is a correlational analytical research design with a cross-sectional approach using the chi-square test. The sample in this study was 50 respondents with a purposive sampling technique. The research results showed that the majority of respondents had a good level of knowledge, namely 35 people (70%), and 30 respondents (60%) had motivation in the good category. Based on the results of the chi-square statistical test, it was found that the p-value was 0.000, so the p-value < 0.05 0.000 < 0.05, where H0 was rejected and Ha was accepted, which means there is a significant relationship between knowledge and motivation and adherence to taking medication. in pulmonary TB patients at Malahayati Hospital, Medan. It is hoped that, from this research, respondents will be able to increase their knowledge and motivation regarding pulmonary TB and always maintain control over medication adherence.